The Effectiveness of Leadership Policies in Creating a Digital Library System - Hakim, Fikri; Siddiqui, Zaid Haidary (Islamic Educational Management Programme, 2024)
Purpose: This research paper aims to investigate potential solutions to school library problems by leveraging digital transformation and implementing effective digital-based library development strategies. Due to the rapid development of technology, traditional school libraries face numerous obstacles that hinder their ability to meet the changing needs of students and teachers. This study examines how digital transformation can address these challenges and improve school library functionality and effectiveness. Methods: The research methodology consists of a comprehensive literature review, case studies, and an analysis of digital library development best practices. Findings: The paper identifies significant challenges facing school libraries, such as limited resources, outdated materials, insufficient access to information, and low user engagement. Incorporating technology into library services and resources, it examines how digital transformation can mitigate these problems. Implementing digital platforms, online databases, e-books, multimedia resources, and interactive learning tools are effective strategies for the development of digital-based libraries. By exploring solutions to school library problems through digital transformation and providing strategies for effective digital-based library development, this paper aims to contribute to the improvement of school library services, empowering students and educators with access to current information, promoting digital literacy, and fostering a dynamic learning environment